Fear of loss through Oasis’ song “Stand by Me and “Don’t go away” - Ignatius Lingga Dwantoro; M. Fadla Nur Kholbi Gifari; Euis Meinawati (Universitas Islam Negeri Palopo, 2026)
This research examines the portrayal of loss anxiety in Oasis’s songs “Stand by Me” and “Don’t Go Away.” Employing a qualitative descriptive approach, the study examines song lyrics as primary data to reveal how